Safety Tech Enterprise : Utility Belt For Construction Worker / Luqman Al Hakim Zainal ...[et al.] - Zainal, Luqman Al Hakim; Abdul Mutallib, Muhammad Shafiq; Abu Talib, Muhammad Afif; Zainal Abidin, Muhammad Zulfadli; Mior Zulharmin, Mior Darwisy Rusyaidi (2017)
Differences in size and shape make this utility belt looks interesting and suitable to serve for any occasion. The light and dry texture gives an opportunity to this belt to be one of marketable product as people love simple things especially safety product. Moreover, the simple steps and ingredients give a lot of benefits to our company and we are highly confident that our market can be easily developed and spread in Malaysia. T make it more attractive and interesting, we decided to make some innovative by implying our creativity and modern element in this utility belt making done some research that Malaysia is one of developed country an busy during day time. So, with our new innovation, they can just us it easily when they work. Easy and simple as that. Our business is expected to commence on 2018 and our vision is to make our company a well-k own, established and satisfied by our customer in order to expand our utility belt to attract other hardware company to deal with us with a better price. This will be realized by the full cooperation and efforts among the partners to prom e company.